Analysis of E-Cadherin Expression in Patients with Esophageal Squamous Cell Carcinoma - Muhammad Ali Soomro, Sidrah, Suresh Kumar, Aneela Faisal Memon, Azhar Ali, Kiran Memon, Kiran, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Esophageal Squamous Cell Carcinoma is a common, deadly cancer. E-Cadherin expression in cancer was investigated along with its relation to parameters like age, gender, differentiation, and mortality. Methodology: A 100-sample descriptive cross-sectional study utilising open EPI software with a 95% confidential interval was obtained. Data was evaluated by SPSS 23.0. Results: E-Cadherin had a negative IRS (immune-reactive score) in 69% of samples, mild in 27%, and moderate in 4%. Chi-square test showed no association between E-cadherin immune-reactive score and the parameters considered. (>P=0.05) Conclusion: This study found that patients with carcinoma express less E-Cadherin but its expression in Esophageal Squamous Cell Carcinoma patients is unrelated to the parameters considered. Keyword: Esophageal Squamous Cell Carcinoma, Immuno-Histochemistry, Haematoxylin, Eosin, E-Cadherin.